2013
DOI: 10.1111/nure.12016
|View full text |Cite
|
Sign up to set email alerts
|

Ginger (Zingiber officinale) and chemotherapy-induced nausea and vomiting: a systematic literature review

Abstract: Chemotherapy-induced nausea and vomiting (CINV) is a common side-effect of cytotoxic treatment. It continues to affect a significant proportion of patients despite the widespread use of antiemetic medication. In traditional medicine, ginger (Zingiber officinale) has been used to prevent and treat nausea in many cultures for thousands of years. However, its use has not been confirmed in the chemotherapy context. To determine the potential use of ginger as a prophylactic or treatment for CINV, a systematic liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 38 publications
3
86
0
15
Order By: Relevance
“…While evidence supports benefits of ginger for seasickness, 18 motion sickness, 19 and postoperative nausea and vomiting, 20 its use in preventing chemotherapy-induced nausea and vomiting is still conflicting. 21,22 Ginger also has been demonstrated to be effective in treating nausea and vomiting in pregnancy to the extent that it is as effective as vitamin B 6 alone. [23][24][25][26][27] The exact antiemetic mechanisms of ginger are still unknown, but in vitro studies revealed antagonistic effects of gingerols on serotonergic 5-HT 3 28,29 and cholinergic M receptors.…”
Section: Ginger and Its Medicinal Effectsmentioning
confidence: 99%
“…While evidence supports benefits of ginger for seasickness, 18 motion sickness, 19 and postoperative nausea and vomiting, 20 its use in preventing chemotherapy-induced nausea and vomiting is still conflicting. 21,22 Ginger also has been demonstrated to be effective in treating nausea and vomiting in pregnancy to the extent that it is as effective as vitamin B 6 alone. [23][24][25][26][27] The exact antiemetic mechanisms of ginger are still unknown, but in vitro studies revealed antagonistic effects of gingerols on serotonergic 5-HT 3 28,29 and cholinergic M receptors.…”
Section: Ginger and Its Medicinal Effectsmentioning
confidence: 99%
“…The reported adverse effects of ginger include abdominal discomfort, heartburn, diarrhea, and inhibition of platelet aggregation leading to bleeding; however, these are of a more theoretical interest. 35,39 …”
Section: Methodsmentioning
confidence: 99%
“…39 The two studies that failed to show a benefit were severely flawed. The first study enrolled only 36 participants, of which 13 were excluded as a result of nonadherence.…”
Section: Methodsmentioning
confidence: 99%
“…Sind die Zellen nach dem Au auen intakt, hat die Implantation die gleichen Erfolgschancen wie bei frisch befruchteten Eizellen. Die Schwangerscha srate wird in Übersichtsarbeiten mit 25-59% bezi ert [1,2].Eine noch nicht so lange praktizierte Alternative ist das Einfrieren unbefruchteter Eizellen, das durch Fortschritte in der Konservierungstechnik heute ebenfalls als sicher und nicht mehr experimentell gelten kann [3]. Die Überlebens-und Befruchtungsraten entsprechen publizierten Daten zufolge etwa denjenigen frischer Eizellen [4,2] …”
unclassified